ANALYSIS OF THE WORK ENVIRONMENT AND WORK STRESS ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE - Ni Nyoman Menuh; Ayu Sri Dewi Wahyuni; Ni Ketut Karwini; Ida Bagus Ngurah Wimpascima (Bajang Institute, 2022)
The work environment must run well and work stress must be managed properly so that employee performance can be achieved according to the duties and functions of an office. The purpose of this study was to determine the analysis of the work environment and work stress and their implications for employee performance at the Bali and Nusra Ecoregional Development Control Center Office. The type of data used in this study is qualitative and quantitative data with primary data sources and using data analysis techniques, namely classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this study indicate that the work environment has a significant positive effect on employee performance and work stress has a significant negative effect on employee performance.